Determining the status of preconception care model in pregnant woman of Gorgan city (North of Iran) using structural equation modeling (SEM) - Narjes Sadat Borghei; Tayebeh Ebady; Roghaieh Bayrami; Roya Nikbakht (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Preconception reduces unplanned pregnancies and plays an important role in reducing maternal and infant mortality. Considering the importance of these care services, this study was conducted to determine the status of preconception care (PCC) model with Structural Equation Modeling (SEM). MATERIALS AND METHODS: This cross-sectional descriptive study was conducted on 394 pregnant women referring to Gorgan's health centers. Samples were selected by multi-stage stratified sampling method. The instrument used in this research was a researcher-made questionnaire by Bayrami. Data were analyzed using R software version 4.1.4. Structural equation modeling (SEM) with weighted least square mean and variance method was used to fit the conceptual model and the significance level of the tests was considered 0.05. RESULTS: The results showed that PCC model was deemed appropriate as optimum conditions indicators of goodness of fit; knowledge with a coefficient of 0.182 leads to self-efficacy (SE), and SE affects the accessibility of facilities with a coefficient of 0.465 and the expected outcome with a coefficient of 0.500. After facility structure with a coefficient of 0.500, SE construct with a coefficient of 0.215 had the most effect on performing PCC behavior. CONCLUSIONS: Facilities and SE as a key element of empowerment have an important role in promoting PCC. Identifying the factors associated with this care appears to help health policymakers to planning for these caregivers more precise and sensitive.